Structural design of microbicidal cationic oligomers and their synergistic interaction with azoles against Candida albicans - Yuan, Yuan (2019)
Membrane-disrupting synthetic antimicrobial polymers have been well developed as antimicrobial peptide (AMP) mimics to mitigate antimicrobial resistance (AMR). However, synthetic polymers possess inherent drawbacks, being a mixture of different chain lengths, which restricts their clinical applications. In fact, synthetic oligomers with defined chain length and molecular structure could be better representatives of AMPs. Herein, a series of novel imidazolium-ammonium oligomers developed in this work exhibit excellent broad spectrum antimicrobial activity, specifically the salient structure dependent high efficiency against C. albicans. Moreover, synergistic effect emerged when the combined azoles and synthetic oligomers were applied against C. albicans. The detail structural coupling between azoles and oligomers was scrutinized through molecular dynamics simulations to unravel the interaction details with the atomistic resolution. The labile interaction between oligomer and azoles facilitated the transfer of drug into fungal cells, which can be a synergistic solution to prevent the development of resistance on C. albicans.